A multifunctional flame-retardant TA-MXene based nanocoating for cotton fabric - Zeng, Qingtao; Wang, Binglin; Lai, Xuejun; Li, Hongqiang; Chen, Zhonghua; Zeng, Xingrong; Zhang, Liqun (Progress in organic coatings, 2024)
Ti3C2Tx (MXene) is an ideal thermoelectric responsive fire-warning material but subject to its poor anti-oxidation and unsatisfied flame-retardant efficiency. Herein, a novel tannic acid (TA) decorated MXene (TA-MXene) with good anti-oxidation was fabricated and then used to prepare multifunctional flame-retardant cotton fabric (MFR@CF) combined with antimony potassium tartrate and polydimethylsiloxane. MFR@CF exhibited temperature-sensing and fire-warning performance. Moreover, MFR@CF showed superior flame retardancy with limiting oxygen index of 29 %. In addition, MFR@CF also possessed good thermal camouflage and self-cleaning performance, showing great application prospect in intelligent clothing and firefighting. Our work provides a new insight for preparing multifunctional smart firefighting CF. [Display omitted] •A novel tannic acid decorated MXene (TA-MXene) with good anti-oxidation was fabricated.•Multifunctional flame-retardant cotton fabric (MFR@CF) was obtained.•TA-MXene endowed MFR@CF with temperature-sensing and fire-warning performance.•TA-MXene significantly improved flame retardancy of MFR@CF.•MFR@CF exhibited good thermal camouflage and self-cleaning performance.